2011
DOI: 10.1177/0091270010381497
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin, a Dipeptidyl Peptidase-4 Inhibitor, Does Not Affect the Pharmacokinetics of Ethinyl Estradiol or Norethindrone in Healthy Female Subjects

Abstract: Sitagliptin is a dipeptidyl peptidase-IV (DPP-4) inhibitor used for the treatment of patients with type 2 diabetes mellitus. This randomized, placebo-controlled, 2-period, crossover study evaluated the effect of sitagliptin on the pharmacokinetics of 17 α-ethinyl estradiol (EE(2)) and norethindrone (NET) in healthy female subjects who were receiving oral contraceptives for >3 months prior to enrollment. A total of 18 subjects with normal menstrual cycles received the oral contraceptive pill ORTHO-NOVUM(®) 7/7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In clinical trials, the DPP-4 inhibitor, sitagliptin, improved fasting and postprandial glycaemic control and measures of β-cell function in patients with type 2 diabetes, with minimal effects on measures of insulin resistance/ sensitivity (30,31) . Metformin has been found to increase GLP-1 levels in humans (32,33) . Sulfonylurea have the advantage of being quite effective in blood glucose lowering, with an almost instant onset of the effect after start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, the DPP-4 inhibitor, sitagliptin, improved fasting and postprandial glycaemic control and measures of β-cell function in patients with type 2 diabetes, with minimal effects on measures of insulin resistance/ sensitivity (30,31) . Metformin has been found to increase GLP-1 levels in humans (32,33) . Sulfonylurea have the advantage of being quite effective in blood glucose lowering, with an almost instant onset of the effect after start of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In phase 1 clinical pharmacology studies, sitagliptin was not found to meaningfully alter the PK of metformin, simvastatin, warfarin, oral contraceptives, rosiglitazone, or glyburide; these studies provide in vivo evidence for a low propensity of sitagliptin for perpetrating drug interactions with substrates of human organic cation transporter, CYP3A4, CYP2C8, and CYP2C9 . Multiple doses of sitagliptin slightly increased plasma immunoreactive digoxin concentrations; however, these increases are not considered likely to be clinically meaningful .…”
mentioning
confidence: 88%
“…24 In phase 1 clinical pharmacology studies, sitagliptin was not found to meaningfully alter the PK of metformin, simvastatin, warfarin, oral contraceptives, rosiglitazone, or glyburide; these studies provide in vivo evidence for a low propensity of sitagliptin for perpetrating drug interactions with substrates of human organic cation transporter, CYP3A4, CYP2C8, and CYP2C9. [25][26][27][28][29][30][31] Multiple doses of sitagliptin slightly increased plasma immunoreactive digoxin concentrations; however, these increases are not considered likely to be clinically meaningful. 32 In a population PK analysis of phase 1 and phase 2b studies, 83 concomitantly administered medications were screened for potential effects on sitagliptin PK; none of the evaluated medications was found to meaningfully alter sitagliptin plasma concentrations.…”
mentioning
confidence: 99%
“…The hepatic metabolism of sitagliptin is minimal (mainly by cytochrome P450 3A4) and it is largely (70-80%) excreted by the urine in its unchanged form, with a halflife of around 12 hours [135]. As a result of its metabolism and elimination, dose adjustment is required in patients with severe renal impairment, but not in those with mild or moderate renal or hepatic impairment [136,137]. No dosage adjustment is necessary on the basis of age, gender, race, or body mass index; in addition, sitagliptin has a low propensity for pharmacokinetic drug interactions [93].…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 99%